Meningkatkan Kinerja Pegawai Kantor Kelurahan Kuta, Badung-Bali: Pendekatan Gaya Kepemimpinan, Motivasi dan Suasana Kerja - Ida Bagus Gede Udiyana; Ni Made Eni Indra Yanti; Ni Nyoman Seri Astini; Ni Ketut Laswitarni; I Nyoman Parta; Ida Bagus Ngurah Wimpascima (Universitas Warmadewa, 2023)
The purpose of this study was to determine and analyze the leadership style, motivation, and work atmosphere influence on the performance of head-village Office employees, partially and simultaneously. This research was conducted at the Kuta Village Office, Badung Regency with a sample size of 36 people. The data analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear regression analysis, t tests and F tests assisted by the SPSS program. The results of this study indicate that partially and simultaneously leadership style, work motivation and work atmosphere have a positive and significant effect on employee performance at the Kuta Village Office, Badung-Bali. So that in an effort to improve employee performance it is recommended that leaders need to involve subordinates in making decisions, give awards to outstanding employees and create a conducive work atmosphere.